Development of an E-Commerce Website to Empower Kampung Lawas Maspati SMEs - Mega Cattleya; Rizqi Novita Sari; Yekti Condro Winursito (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The rapid advancement of digital technology has significantly influenced how small and medium enterprises (SMEs) connect with consumers. Kampung Lawas Maspati SMEs encounter obstacles in expanding their market due to limited online visibility and reliance on conventional sales approaches. This study aims to develop an e-commerce website that addresses these challenges by focusing on user-centered innovation. Using the Design Thinking method, which includes stages such as empathizing, defining, ideating, prototyping, and testing, user needs and challenges were explored through interviews, surveys, and observations to inform the website development process. The resulting platform is intuitive, responsive, and accessible, enabling SMEs to display their products, manage transactions, and engage with customers effectively. The application of this method not only improves market reach but also strengthens the competitiveness and digital literacy of Kampung Lawas Maspati SMEs. Evaluation results show a high level of consumer satisfaction, reaching 91.87%, indicating that the developed website effectively meets user expectations and supports SME digital transformation.